Learning to solve problems : an instructional design guide. - Jonassen, David H., 1947-2012 (San Francisco : Pfeiffer, 2004)
Problem solving is a key skill that we all use every day to solve simple and complex problems. However, little education or training challenges learners to solve problems and almost none engages learners in the types of problem solving encountered in everyday and professional situations. Learning to Solve Problems is a much-needed book that describes models for designing interactive learning environments to support how to learn and solve different kinds of problems. Using a research-based approach, author David H. Jonassen-a recognized expert in the field-shows how to design instruction to support three kinds of problems: story problems, troubleshooting, and case and policy analysis problems. Filled with models and job aids, this book describes different approaches for representing problems to learners and includes information about technology-based tools that can help learners mentally represent problems for themselves. Jonassen also explores methods for associating different solutions to problems and discusses various processes for reflecting on the problem-solving process. Learning to Solve Problems also includes three methods for assessing problem-solving skills: performance assessment, component skills, and argumentation.
Keywords: Probleemoplossend denken